TINJAUAN YURIDIS TINDAK PIDANA PENYEROBOTAN TANAH ADAT DI KABUPATEN TORAJA UTARA - Jenri Ranteallo; Yana Sukma Permana (The Juris, 2022)
Land grabbing is not a new problem that often occurs in Indonesia. Unlawful land grabbing is an unlawful act and can be classified as a criminal act. The formulation of the problem in this study is the regulation of customary land ownership in North Toraja district and legal settlement of criminal acts of land grabbing in North Toraja district. Ownership of customary land is marked by physical possession and recognition as stated in Article 24 paragraph (2) of Government Regulation Number 24 of 1997. Regarding customary land or Toraja indigenous people, it is called tongkonan land. The North Toraja government has ratified Regional Regulation number 1 of 2019 concerning "Recognition and protection of the rights of indigenous peoples" in which the regulation has concretely regulated the system of land tenure and use. There are several stages of legal settlement of customary land grabbing in North Toraja Regency, both within the scope of customary law, namely mediation through the customary institution where the tongkonan land is located and positive law, namely through the courts.